Phytochemical characterization and antioxidant activity of Opuntia microdasys (Lehm.) Pfeiff flowers in different stages of maturity - Chahdoura, Hassiba (2014)
Chemical composition and antioxidant activity of Opuntia microdasys flowers in different maturity stages was evaluated. Fructose, glucose, sucrose and trehalose were found; oxalic, quinic, malic, and citric acids were also detected; five hydroxycinnamoyl, two kaempferol and six isorhamnetin derivatives; 23 fatty acids were quantified in all stages, except C20:2, which was only found in post flowering stage (F3); alpha-, beta-, gamma-, and delta-tocopherols were quantified in all samples. The highest contents in soluble sugars and phenolic compounds were detected in full flowering stage (F2), while organic acids and tocopherols were predominant in vegetative stage (F1). The highest levels of saturated, monounsaturated and polyunsaturated fatty acids were found in F3, F2 and F1, respectively. F1 gave the highest antioxidant activity. Principal components analysis showed clearly individualized groups corresponding to each flowering stage, identifying the most distinctive features, which might be useful to select a flowering stage for incorporation in functional foods. (C) 2014